2011
DOI: 10.1007/s11661-011-0741-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Thermoelectric Magnetic Convection on the Solidification Structure During Directional Solidification under Lower Transverse Magnetic Field

Abstract: This work investigated the thermoelectric magnetic convection (TEMC) during directional solidification under a transverse magnetic field numerically and experimentally. Numerical results show that the TEMC will form in liquid near the liquid/solid interface and in the dendritic network. The value of the TEMC mainly depends on the crucible diameter, the temperature gradient, and the magnetic field intensity. The value of the TEMC increases as the crucible diameter and the temperature gradient are increased. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Macrosegregation occurs normal to the magnetic field orientation and to the thermal gradient. Descriptions of the mechanism have been given by authors of these experimental findings [4,6], supported with idealised steady state 2-dimensional models of TEMHD. They suggest that this behaviour is caused by interdendritic flow transporting high concentration of solute out of the mushy zone.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Macrosegregation occurs normal to the magnetic field orientation and to the thermal gradient. Descriptions of the mechanism have been given by authors of these experimental findings [4,6], supported with idealised steady state 2-dimensional models of TEMHD. They suggest that this behaviour is caused by interdendritic flow transporting high concentration of solute out of the mushy zone.…”
Section: Introductionmentioning
confidence: 87%
“…In the presence of a transverse magnetic field, macrosegregation on the sample scale has been observed for both in situ thin sample experiments [4] and post-mortem analysis of rod shaped samples [4,5,6]. Macrosegregation occurs normal to the magnetic field orientation and to the thermal gradient.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, the magnitude of the changes had a material dependency which could be attributed to the variation in thermoelectric power of the various alloys examined. More recently, microstructural changes have been observed over a wide range of magnetic field intensities from low-moderate (O(1T)) field strengths [19][20][21][22] to higher (O(10T)) strengths [23][24][25]. Furthermore, direct in situ observations of solidification under a relatively low magnetic field have shown indications of TEMHD flow at the meso scale [26].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is known as Thermoelectric Magnetohydrodynamics (TEMHD) and experimental results for both high 1) and low 2) magnetic fields have shown that the application of a constant external magnetic field can cause fragmentation, acting to produce a finer grained casting, with a concomitant increase in yield strength. However, the undesirable effect of macro-segregation [3][4][5] and freckling 6) have been observed. Both of these effects can be attributed to the convective transport of heat and mass, altering the solidification process.…”
Section: Introductionmentioning
confidence: 99%